Hubungan antara Intensitas Bermain Game Online dengan Perilaku Disiplin Warga Belajar pada Pelatihan Otomotif - Ramadhani Latesa Muraza; Wisroni Wisroni (RC-INSTITUT, 2020)
This research is motivated by the low learning discipline of the learning citizens, this is related to the high intensity of playing online games for the learning citizens of the Mandiri Racing Team. This study discusses, 1) to see the complexity of playing online games, 2) to see the discipline of learning competence, 3) to see the relationship between the intensity of playing online games with the discipline of learning at the Independent Racing Team Course Institute. This type of research is quantitative correlational. The study population was learning citizens registered with the Institute of Independent Racing Team Courses, totaling 75 learning residents. Samples were taken as much as 40%. The number of samples is 30 people. The sampling technique uses cluster random sampling. The technique of collecting data through a questionnaire, the data collection tool consists of agreed lists. This research data analysis technique uses percentages and product moments. The results of this study can be seen (1) the higher intensity of playing online games for learning citizens at the Institute of Independent Team Racing Course, (2) the low discipline of citizens learning the learning process, and (3) requires a significant relationship between online play games with the learning discipline of the Race Team Independent Course. Suggestions in this study are 1) for citizens to learn in order to improve discipline in learning at the Independent Course Team Race Course, 2) for instructors to be able to increase knowledge about learning discipline for citizens to learn the Independent Course Team Race Course, 3) for parents of learning citizens in order to be a reference and knowledge about disciplining children's activities.